Analyzing the Impact of Fly Ash Additive Ratio on Lubricant Properties - Bui, Tuan Anh; Le, Duc-Do; Tran, Duc-Toan; Nguyen, Manh-Toan; Tran, Van-Thuc; Bui, Ngoc-Tam (Engineering, Technology & Applied Science Research, 2023)
Preventing surface damage is crucial for optimal machine performance, with lubricants and additives playing a vital role in achieving this objective. This study specifically focuses on evaluating the influence of fly-ash additives on the wear resistance of machine components when incorporated into lubricant oil. The experiments were conducted following ASTM standard operating conditions, utilizing the four-ball wear test to measure the scratch width and weight loss of balls using different lubricant oil formulations, including 0, 0.1%, 0.5%, 0.75%, and 1% additive. The findings demonstrate that the inclusion of 0.5% fly ash additive in the lubricant oil results in a significant reduction in both scratch width and weight loss of the balls. However, it should be noted that higher additive ratios may lead to increased scratch width and weight loss due to the agglomeration of the fly ash particles on the sliding surfaces. To achieve optimal effectiveness in reducing friction and wear, it is recommended to carefully control the content of fly ash within an appropriate range. Furthermore, this study highlights the width of scratches on balls as a reliable indicator for assessing the anti-wear properties of oils. The insights gained from this research offer valuable guidance to manufacturers in the selection of suitable anti-wear oils for specific applications. Further investigations could explore the impact of different lubricants and additive ratios to identify the most appropriate lubrication parameters. Overall, this study contributes to a better understanding of the effects of fly ash additives on the performance of lubricant oil and provides practical guidance for optimizing lubrication strategies in diverse industrial contexts.